Exploring Collaborative Health Promotion Services between Public Health Centers and Public Libraries - Tung-Chi Hu; Yu-Wei Chang (Jiàoyù zīliào yǔ túshūguǎn xué, 2017)
The increasing mortality rate of chronic diseases leads to that the World Health Organization advocates the concept of health promotion aiming to correct people's health awareness and behavior and enhance their public health self-control via use of correct health information and educational activities. Among various types of institution in communities, public health centers provide local health promotion services and public libraries are responsible for improving people’s public health information literacy. Because public health centers do not understand the roles of public libraries, and vise versa, no collaborations have been built between them to strengthen health promotion services. The findings of this study showed that public health centers have actively cooperated with various types of institutions, based on interviews with 5 community nurses and 6 librarians. Public libraries have not promoted health information services. A supplementary relationship was found to exist between public health centers and public libraries according to their advantages and disadvantages. In addition, public health centers and public libraries were willing to cooperate to improve health promotion services. A propose consisting of three aspects was formed for policy makers.